Protection of children against sexual offences : Islamic and Malaysia Laws perspectives - Mohammad Hidir bin Baharudin (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2018)
Issues relating to children sexual offences have become a national concern. Under Islamic and Civil laws, every person including the children enjoy their rights. However, the occurrence of such offences has violated and denied the right of the children to live peacefully. Hence, this research aims to examine the rights of children in Islamic and Civil laws that protect them from sexual offences. In addition, this research analyses Malaysian laws regarding children sexual offences as well as the best practices of prevention actions in selected jurisdictions. Therefore, the discussion adopts the doctrinal analysis where the issues examined from the perspective of the Holy Quran, the traditions of the Prophet (PBUH) as primary sources of Islamic laws and follows with the examination of the view of Muslim jurists of four well-known schools of law in Islam as well as the views of contemporary Muslim scholars. This study also includes analysis of relevant statutory provisions, cases (reported and unreported) and other legal and non-legal literatures.